Case Report: Periodic Hypokalemic Paralysis - Nurci Efrilia Safitri; I Made Mahardika Yasa (KHD-Production, 2023)
Hypokalemic periodic paralysis is characterized by muscle weakness or flaccid paralysis followed by low potassium levels (less than 3.5 mmol/L) during the attack. Proper initial management and patient education are mandatory for health workers to manage this case. This study was a descriptive study with a case report approach. This case report includes patients over 18 years receiving health care at the Negara General Hospital and having accessible medical record data. Data collection was carried out consecutively. A case from a 22-year-old man with complaints of weakness in both legs. The examination found lower extremity motor strength 2/2, normal physiological reflexes without pathological reflexes, and a laboratory potassium level of 2.5 mmol/L laboratory results. The patient was then given hypokalemia treatment with KCl intravenously. The patient, in this case, had no clinical condition contraindicated to give potassium. Within 24 hours after potassium administration, the patient showed a significant improvement. Hence, our therapy, in this case, was in line with the theory with a good clinical outcome. Symptomatic therapy in hypokalemic periodic paralysis provides a good clinical outcome. There were no complications or clinical emergencies during treatment.